Pengaruh Return On Equity (ROE), Return On Asset (ROA), Dan Debt To Equity Ratio (DER) Terhadap Corporate Sosial Responsibility (CSR) (Studi pada Sub Sektor Properti yang terdaftar di Bursa Efek Indonesia Tahun 2017-2019) - Nova Suci Indrawati; Ronny Malavia Mardani; Mohammad Rizal (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThe purpose of this study was to determine and analyze the effect of Return On Equity (ROE), Return On Assets (ROA), and Debt To Equity Ratio (DER) on Corporate Social Responsibility (CSR). By using the population of all property companies listed on the Indonesia Stock Exchange in 2017-2019, there were 62 companies listed as the population. Then a sample of 27 companies was taken using a purposive sampling technique with the criteria of companies listed on the IDX, having financial statements related to variables during 2017-2019, as well as property companies using the rupiah currency.The results in this study indicate that there is a partial effect of Return On Equity (ROE) on Corpotare Social Responsibility (CSR) but the variables Return On Assets (ROA) and Debt to Equity Ratio (DER) have no effect on Corporate Social Responsibility (CSR). Keywords: Return On Equity (ROE), Return On Assets (ROA), Debt To Equity Ratio (DER), Corporate Social Responsibility (CSR)